2009
DOI: 10.1111/j.1463-1318.2008.01562.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 4% icodextrin solution on adhesiolysis surgery time at the Hartmann’s reversal: a pilot, multicentre, randomized control trial vs lactated Ringer’s solution

Abstract: Icodextrin treatment resulted in a decreasing trend in adhesiolysis time. The use of 4% ID solution in peritonitis patients seemed to be safe. Because of larger than expected variations in adhesiolysis times, this pilot study was underpowered to meet the study end-point and further statistical modelling estimated that significance cannot be reached within a reasonable time scale. Other models should be used to evaluate the efficacy of anti-adhesive agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…The safety and efficacy of icodextrin in reducing adhesion formation has been shown in many animal studies [4][5][6][7]. However, few human studies focusing on the efficacy of icodextrin on adhesion prevention have been published to date [9][10][11][12]16]. There have been even fewer studies evaluating the clinical benefits of icodextrin after general surgery, the results of which seem to be somewhat conflicting [17,18].…”
Section: Discussionmentioning
confidence: 93%
“…The safety and efficacy of icodextrin in reducing adhesion formation has been shown in many animal studies [4][5][6][7]. However, few human studies focusing on the efficacy of icodextrin on adhesion prevention have been published to date [9][10][11][12]16]. There have been even fewer studies evaluating the clinical benefits of icodextrin after general surgery, the results of which seem to be somewhat conflicting [17,18].…”
Section: Discussionmentioning
confidence: 93%
“…In a study in humans, Kössi et al [24] found that icodextrin treatment reduced adhesion formation-post surgery. Adhesions are a common complication of serious peritonitis especially those caused by pseudomonas and enteric organisms.…”
Section: Discussionmentioning
confidence: 98%
“…Kossi demonstrated that icodextrin was able to reduce the number of adhesions and adhesiolysis time during Hartmann reversal but without reaching statistical significance. 23 Further data were obtained by Ariel Registry which enrolled 7,000 patients operated with open and laparoscopic surgery for oncological and non-oncological diseases. These large numbers confirmed the safety of this fluid with regard to bowel leaks and wound dehiscence.…”
Section: Discussionmentioning
confidence: 99%